Better living challenge 2 : addressing upgrades to informal settlements in South Africa - Hatendi, Tsitsi; Bick, Geoff (London : Graduate School of Business, University of Cape Town, 2018)
The case follows Kelly Arendse, the project manager for Better Living Challenge an NGO that creates innovative products and solutions to informal housing settlements to allow economically and socially marginal groups to improve their housing situation. After the South African government withdraws funding from the project Kelly must now consider where and what strategy she should use to secure funds to continue with her work at Better Living Challenge.
Originally Published InHatendi, T., & Bick, G. (2018). Better Living Challenge 2: Addressing upgrades to informal settlements in South Africa. 2018-1. Cape Town, South Africa: Graduate School of Business, University of Cape Town.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Arendse, Kelly; Better Living Challenge -- Management; Corporations -- Finance -- Case studies; Business enterprises -- Finance -- Case studies; Non-governmental organizations -- Management -- Case studies; Squatter settlements -- Equipment and supplies